Fostering team creativity: Perspective taking as key to unlocking diversity's potential. - Hoever, Inga J.; van Knippenberg, Daan; van Ginkel, Wendy P.; Barkema, Harry G. (Journal of Applied Psychology, 2012)
Despite the clear importance of team creativity for organizations, the conditions that foster it are not very well understood. Even though diversity, especially diversity of perspectives and knowledge, is frequently argued to stimulate higher creativity in teams, empirical findings on this relationship remain inconsistent. We have developed a theoretical model in which the effect of a team's diversity on its creativity is moderated by the degree to which team members engage in perspective taking. We propose that perspective taking helps realize the creative benefits of diversity of perspectives by fostering information elaboration. Results of a laboratory experiment support the hypothesized interaction between diversity and perspective taking on team creativity. Diverse teams performed more creatively than homogeneous teams when they engaged in perspective taking, but not when they were not instructed to take their team members' perspectives. Team information elaboration was found to mediate this moderated effect and was associated with a stronger indirect effect than mere information sharing or task conflict. Our results point to perspective taking as an important mechanism to unlock diversity's potential for team creativity.